2008
DOI: 10.1007/s00040-008-1004-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing daily foraging activity of Vespula germanica (Hymenoptera, Vespidae) in Mediterranean Australia

Abstract: In social insects, workers forego reproduction in favour of foraging and other tasks to promote growth of the whole colony. Maximising individual work effort is limited by the physical constraints on foraging outside the nest. Previous studies of factors influencing activity in social insects suggest that light intensity, ground and air temperature, relative humidity, solar radiation, wind speed and/or rainfall may be important. This study aimed to determine which environmental factors influence foraging in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 36 publications
8
77
0
7
Order By: Relevance
“…V. crabro is also active with low light intensity but in a higher propensity (Kelber et al., 2011). Second, the worker activity is driven by weather conditions that is quite classical in Vespidae (Canevazzi & Noll, 2011; de Castro, Guimaraes, & Prezoto, 2011; Cruz, Giannotti, Santos, Bichara Filho, & Resende, 2006; Kasper, Reeson, Mackay, & Austin, 2008; da Rocha & Giannotti, 2007). The observed enhancement of the hornet activity during the day with a maximum around noon, already observed by video analysis (Monceau et al., 2017), can be either attributed to an increase in temperature or in UVB solar irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…V. crabro is also active with low light intensity but in a higher propensity (Kelber et al., 2011). Second, the worker activity is driven by weather conditions that is quite classical in Vespidae (Canevazzi & Noll, 2011; de Castro, Guimaraes, & Prezoto, 2011; Cruz, Giannotti, Santos, Bichara Filho, & Resende, 2006; Kasper, Reeson, Mackay, & Austin, 2008; da Rocha & Giannotti, 2007). The observed enhancement of the hornet activity during the day with a maximum around noon, already observed by video analysis (Monceau et al., 2017), can be either attributed to an increase in temperature or in UVB solar irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria das espécies de abelhas aumenta a atividade de forrageio nos períodos em que a temperatura e a intensidade luminosa estejam elevadas, e tanto a umidade relativa do ar, quanto a velocidade do vento estejam baixas (soMMeijeR et al 1983;hiLáRio et al 2000;kasPeR et al 2008). Contudo, cada espécie está adaptada a condições climáticas específicas (CoRbet et al 1993), que muitas vezes resulta no uso dos mesmos recursos florais de forma partilhada (WiLMs et al 1996).…”
Section: _____________________________________unclassified
“…A variety of studies has demonstrated the influence of weather conditions on social wasp foraging and nearly all of them point to temperature as the key factor influencing foraging [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]38]. We found a great influence of temperature on foraging, since there was an increase in the number of foragers simultaneously to the increase of temperature (Figure 3).…”
Section: Temperaturementioning
confidence: 99%
“…Many studies have been done with the purpose of verifying several aspects related to the flight and foraging activity of social wasps, such as daily and seasonal activity of searching for resources, items collected, influence of colony and environment factors on the foraging, and foraging activity behavior patterns [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. The foraging activity of these wasps varies throughout a day and throughout the seasons, but also according to the place where the study is carried out [26].…”
Section: Introductionmentioning
confidence: 99%